Distribution of natural radionuclides activity concentrations in sediment, water and biota from an abandoned tin mining lake of Kampung Gajah, Perak / Norannisak Muhamad Isak - Muhamad Isak, Norannisak (2015)
Former tin mining lakes were expected to have a high degree of pollution due to the presence of natural radionuclides. There is a possibility that radionuclides be transferred between sediment, water and biota as a result of exchanges between them through biological, physical and chemical processes. In spite of this, the local people had consumed fish and shellfish from this lake as their sources of protein. Therefore,this study on Kapal 7 Lake, Perak involved analysis of NORM (238U, 232Th and 40K) activity concentrations in sediment, water and edible part of fish and their linkages between the samples including the assessment of radiological risks. The measurements were done by using high resolution gamma spectrometry system. In addition, the sedimentation rate also had been determined by using Pb method applying Constant Rate of Supply (CRS) model. The sedimentation rate was 0.146 cm/y and the age sediment was found to be about 62 years which was in agreement to the time when the tin mining activity stopped in the area at around late 1960's.Sediment samples had contained higher activity concentrations of 238U, 232Th and 40K compared with world average concentrations (UNSCEAR 2000) which ranging from 170.1 to 287.5, 194.9 to 351.7 and 238.4 to 843.0 Bq/kg, respectively and also not suitable used as building materials by referring to the radiological risk assessment.Moreover, the high level of 238U, 232Th and 40K also had found in water samples which compared with the UNSCEAR (2000) reference values of 0.001 and 0.0005Bq/L, respectively. The range of activity concentrations of 238U, 232Th and 40K in unfiltered and filtered water samples was 0.56 to 1.45, 0.44 to 1.22 and 5.92 to 9.94 Bq/L; 0.41 to 1.06, 0.33 to 0.86 and 4.70 to 9.15 Bq/L,respectively. Additional study on physico-chemical parameters were carried out in order to evaluate the water quality which found to be falling in class I and IIA based on National Water Quality Standard (NWQS). The presence of 238U, 232Th and 40K activity concentrations also had been found in fish samples; ranged from 3.24 to 5.67, 1.42 to 4.48 and 161.9 to 239.7 Bq/kg, respectively. Based on distribution coefficient (Kd) and concentration factor (CF), there has shown that NORM concentrations had been transferred between the samples. On average the ingestion dose for U and Th due to consumption offish samples were below the limit set by UNSCEAR (2000).